The Influence of International Law on the Formation of National Law in Developing Countries - Dhesy Arisandielis Kase (Ipso Jure, 2025)
Globalization has led to an increasingly close legal interconnection between countries, so that the boundaries between national and international laws have become blurred. Developing countries such as Indonesia face major challenges in adapting the domestic legal apparatus to global norms driven by international organizations and multilateral agreements. This study aims to describe how international law influences the formation of national laws in Indonesia, using a descriptive approach through a literature study of ratified regulations and conventions. The findings show that while ratifications of international law such as CEDAW and UNCLOS have encouraged legislative reform, their implementation has often been hampered by legal pluralism, local values, and domestic political interests. In addition, the legal harmonization process often occurs top-down and with minimal public participation, posing a risk of non-adaptive legal transplantation. In this context, international law can be a means of normative domination that ignores local needs if not critically addressed. Therefore, developing countries need to develop a selective and contextual approach to accepting the influence of international law, so that the formation of laws remains based on the principles of sovereignty, social justice, and the sustainability of national law.